European Earwig Forficula auricularia Linnaeus (Insecta: Dermaptera: Forficulidae) - John L. Capinera (EDIS)
EENY-483, a 6-page illustrated fact sheet by John L. Capinera, is part of the Featured Creatures collection. It describes this predatory, omnivorous insect with pincer-like cerci (forceps) – distribution, description and life cycle, behavior, hosts, damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, October 2010.